The effectiveness of waste management policy governance in Indonesia: Between national targets and local achievements - Balqis Mira Firdausy (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The problem of waste management in Indonesia is still a serious challenge in realizing sustainable development. Although the government has set the Indonesia Clean Waste 2025 target target through Presidential Regulation No. 97 of 2017 concerning the National Policy and Strategy on Household and Similar Household Waste Management (Jakstranas), the implementation achievements at the regional level have not shown optimal results. Methods: This article uses a descriptive qualitative approach with content and interpretive analysis of secondary data from policy documents, performance reports, and academic publications for the 2019–2024 period. The analytical framework integrates the policy implementation effectiveness model of George C. Edwards III (1980) and the Collaborative Governance model of Ansell and Gash (2007). Findings: The results of the analysis show that the effectiveness of the implementation of waste management policies in Indonesia is still low to moderate. The main obstacles include non-participatory policy communication, limited regional resources and funding, weak inter-agency coordination, and low participation of the community and the private sector. However, some areas, such as Surabaya and Bekasi, have shown relatively successful collaborative practices in encouraging public participation and local innovation. Conclusion: The effectiveness of the implementation of waste management policies in Indonesia cannot be said to be effective, either in achieving national targets or in their implementation at the local level. Facilitative leadership, inclusive institutional design, and transparent policy communication are needed so that national and equitable targets can be implemented at the local level. Another thing is that the governance of waste management policies is highly dependent on the power of multi-level collaboration between the central government, local governments, the private sector, and the community. Novelty/originality of this article: This article offers the integration of two governance models—Edwards III and Ansell & Gash—in analyzing the effectiveness of environmental policy implementation in Indonesia and providing practical lessons from Singapore's experience to strengthen cross-sectoral collaboration in waste management.